The business of genocide : the SS, slave labor, and the concentration camps - Allen, Michael Thad (University of North Carolina Press, 2002)
An exploration of the bureaucrats behind the Nazi slave labour camps. It contradicts the assumption that the SS forced slavery upon the German economy, demonstrating that instead industrialists actively sought out the Business Administration Main Office as a valued partner in the war economy